2022
DOI: 10.1371/journal.pone.0269473
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of syphilis infection among pregnant women attending antenatal care in hospitals of Wolaita zone, Southern Ethiopia, 2020

Abstract: Objective of the study The objective of this study was to identify determinants of syphilis infection among pregnant women attending antenatal care in hospitals in the Wolaita zone, Southern Ethiopia,2020. Methods An unmatched facility-based case-control study was conducted among pregnant women who received antenatal care at four randomly selected hospitals from September 1 to October 30, 2020. A two-stage sampling technique was used in the selection of hospitals and study participants. The data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Among those who had multiple sexual partners, 46.7% were found to have syphilis infection. Our findings are consistent with the studies done in northwest and southern Ethiopia [ 17 , 18 ]. Inconsistence was with the study done in Brazil [ 19 ] and the one done in Cameroon [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
“…Among those who had multiple sexual partners, 46.7% were found to have syphilis infection. Our findings are consistent with the studies done in northwest and southern Ethiopia [ 17 , 18 ]. Inconsistence was with the study done in Brazil [ 19 ] and the one done in Cameroon [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
“…All women in the case group were treated during pregnancy, childbirth, or puerperium. The therapeutic schemes are described below: 78% (46) benzathine benzylpenicillin 2.4 million international units administered in three-doses; 1.7% (01) benzathine benzylpenicillin 2.4 million international units administered as a single-dose; 3.4% (02) doxycycline 100 mg in postpartum women due to penicillin allergy (reactive result occurred at delivery or puerperium) and 18.6% ( 11 ) had no details of the therapeutic scheme or number of doses. In the case group, 84.7% ( n = 50) had newborns diagnosed with CS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that risk factors for GS are: one to three PNC visits (8), less education, a history of abortion (9,10), previous sexually transmitted infections (8,10,11), multiple sex partners (9)(10)(11), unmarried status, travel of sex partner in the past 12 months (10), substance use (11). However, only one case-control study has assessed programmatic (access and quality of prenatal care) factors (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…("Syphilis in Pregnancy," 2022). The spirochete Treponema palladium causes the widespread sexually transmitted illness known as syphilis (Lendado et al, 2022). Although this illness is typically thought to be sexually transmitted, it can also infrequently spread through blood transfusions, non-sexual contact, and even in utero (Wubete et al, 2019).…”
Section: Introductionmentioning
confidence: 99%